2022-RA-1081-ESGO A prospective study to evaluate the agreement of high-risk human papillomavirus detections by vaginal self-sampling and physician-sampling. (20th October 2022) - Huang, Huei-Jean; Chou, Hung-Hsueh; Lai, Chyong-Huey; Wu, Ren-Chin; Yang, Lan-Yan
Abstract : Introduction/Background: Various human papillomavirus (HPV) testing using physician-collected cervical samples have been approved for cervical screening. The COVID-19 pandemic highlights the need of self-sampling test for high-risk patients who are unwilling to participate routine screening program. The aim of clinical trial is to introduce a new 'Hygeia Touch Self Sampling Kit for Women' and evaluate the agreement of high-risk human papillomavirus (hrHPV) detections between vaginal self-sampling via Kit by patients and physician-collected cervical sampling. Methodology: Women aged 21–65 years without hysterectomy were enrolled by stratification: normal population and participants with Pap smear ≥ASCUS or cervical biopsy ≥ CIN 1 (ratio=1:10). All the participants had video-guided self-collected vaginal sampling, then physician-collected cervical sampling. The hrHPV types include types16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 66, 68. The primary endpoint is to evaluate the agreement of hrHPV detection between self-sampling via Kit and physician-cervical sampling using Cohen's kappa statistic, and the sensitivity and specificity of detection methods were also compared. Results: There were 1170 eligible participants. For the detection of hrHPV and any specific HPV type of 27 types, the concordance between self-collected sampling and physician was high (Cohen's kappa 0.75, 95% CI 0.72–0.79 and 0.75, 95% CI 0.71–0.79, respectively). The detection rate of ≥ cervical intraepithelial neoplasia 2 (CIN2+) via HPV testing between self-collected vaginal samples and physician-collected cervical samples were similar in sensitivity (85% vs 89%, relative accuracy 95%), specificity, positive predictive value, and negative predictive value. Two participants had mild anxiety and seven participants had mild perineal pain, and the symptoms subsided after sampling. The adverse event is 0.7%. Conclusion: These results demonstrate good agreement for detecting hrHPV and HPV between self-collected vaginal swabs and physician sampled cervical specimens in detecting CIN2+ lesions.